Manajemen Waktu Lembaga Pendidikan Islam dalam Perspektif Al- Qur’an - Ceceng Ahmad; Irfan Al Hakim (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This article discusses the Qur'anic view of time management. This theme is studied based on the al-Qur'an's vocabulary which represents time terms such as the word, Al-Ajal, Ad-dahr, Al-waqt, andwords of time to swear such as the editors of al-layl, al-duha, al-subh, al - nahar, al - fajr, and al-'asr aslanguage analysis. The word is used to see the factors that underlie the primacy of time managementso that it gets priority in activities. Based on the discussion carried out, the Qur'anic view of time.Time is something so important that Allah repeatedly mentions it in the Koran, both showing a clearduration and a clear boundary. Time management presents the skills, tools, and ability to do the rightthing at the right time, with minimal effort and minimal resources, effective and efficient, throughwhich one can achieve personal goals and values that are prioritized factors that support the priorityof time in conducting management time is to do time planning, organizing time, and evaluating time.Keywords: Time Management, Islamic Education, Al-Qur'an